Development of a behaviour change intervention to promote sanitation and latrine use in rural India - Usman Talat; Luke Ravenscroft; Ivo Vlaev (BMC, 2023)
Abstract Background Across developing countries poor sanitation is associated with disease often found widespread in rural populations. Objectives This objective of this study was to conduct a formative research and feasibility evaluation of the behavioural intervention designed to improve latrine use in rural India. Methods Study conducted in four villages of Rajasthan, where latrine use is low and open defecation may spread disease. To identify the intervention a literature review was conducted, a survey of 497 households, and focus groups in village households (8-10 women and children). Seven focus groups with 63 women were conducted. Based on the survey results, the behaviour change intervention is developed utilising the Capability-Opportunity-Motivation-behaviour model and MINDSPACE framework. One intervention component involves psychological aspects that engage villagers through a pledge; the other component is provision of small incentives to facilitate latrine use. Feasibility and acceptability of the intervention was examined in the study population. The 30-day intervention was delivered to women in 38 randomly selected households who despite having a functional latrine did not use it. Thematic analysis, binary logistic regression analysis and feasibility evaluation of the intervention conducted. Post-intervention feedback from 22 participating households was obtained. Results The piloted intervention was feasible and so a revised design is offered. Results driving this evaluation include barriers identified, and used to improved intervention design in the current study. Village authority figures influenced behaviours across the villages and so did factors of convenience (β = 5.28, p < 0.01), relief (β = 5.49, p < 0.01), comfort (β = 2.36, p < 0.01), Construction cost (β=-1.98, p < 0.01) and safety (β = 2.93, p < 0.01) were significant concerns associated with latrine use in the context of prevalent OD in the region. The logistic regression baseline model for the dependant variables indicated a significant increase in latrine use. Based on the feasibility study, the intervention is refined in several ways. Conclusions Our theory-driven approach improves latrine use in Rajasthan and offers a useful tool to facilitate hygiene behaviour.